Korupsi sebagai Musuh Bersama: Merekonstruksi Spiritualitas Anti Korupsi dalam Konteks Indonesia - Simangunsong, Bestian (Sekolah Tinggi Agama Kristen Negeri Toraja, 2018)
Abstract: Indonesian goverment established corruption as an extra ordinary crime. Government produced some policies as a manifestasion to prove that they are serious to overcome the practices of corruption and all of the impact in society. Not only government, church as an institution of religion which rich of moral and ethics views can play their role even to show their responsibilities to construct some formulas to solve some problems related to corruption that occur in the life of nation, society and church. Actually, the synergy between all alements of nation is needed, including the church as an agent of change to raise awareness to understand about corruption and the latent danger of it’s impact. Corruption is the common enemy. It’s also a social concern in Indonesia. So, church as a symbol of a salt and light of the world, has a calling to play the role reconstructing anti-corruption spirituality based on theological dialog and tradition about distributing parjambaran in the context of Batak society.Abstrak: Pemerintah Indonesia menetapkan korupsi sebagai extra ordinary crime. Kebijakan ini sebagai salah satu wujud keseriusan pemerintah mengatasi praktek korupsi dan segala dampak yang ditimbulkannya di tengah masyarakat. Tidak hanya pemerintah, gereja sebagai lembaga agama yang kaya akan ajaran-ajaran moral juga bertanggungjawab untuk menemukan sebuah formula yang dapat mendorong percepatan penyelesaian persoalan-persoalan terkait korupsi yang terjadi di tengah kehidupan bangsa, masyarakat, dan gereja. Dibutuhkan sinergi antara seluruh elemen bangsa, termasuk gereja sebagai agen perubahan untuk menumbuhkan kesadaran di tengah masyarakat akan pentingnya memahami korupsi dan bahaya laten yang ditimbulkannya. Korupsi merupakan musuh bersama dan keprihatinan sosial di tengah Indonesia. Upaya merekonstruksi spiritualitas anti korupsi yang didasarkan pada penekanan integritas dengan mendialogkannya dengan kearifan lokal pembagian parjambaran pada masyarakat Batak merupakan sumbang pikir teologis terhadap perlawanan korupsi.